Hubungan Antara Dukungan Keluarga dengan Tingkat Kecemasan pada Pasien yang Menjalani Kemoterapi di Semarang - Umi Aghni; Dwi Heppy Rochmawati; Wigyo Susanto (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Cancer is still one of the leading causes of death in Indonesia and poses a major challenge in the world of health. Cancer patients undergoing chemotherapy generally face various psychological problems, one of which is anxiety arising from side effects of therapy, uncertainty of treatment, and deterioration of physical condition. This study aimed to analyze the relationship between family support and anxiety levels in patients undergoing chemotherapy. The research design uses a quantitative approach with a cross-sectional method. The research sample amounted to 40 chemotherapy patients at RSI Sultan Agung Semarang who were selected using a total sampling technique. The research instruments were in the form of family support questionnaires and the Hamilton Anxiety Rating Scale (HARS). Data analysis was carried out using the Marginal Homogeneity test. The results showed that most patients received family support in the moderate to high category (75%) and experienced mild to moderate levels of anxiety (70%). Based on statistical tests, a value of p = 0.001 was obtained, which showed a significant relationship between family support and anxiety levels in chemotherapy patients. The conclusion of this study confirms that good family support plays an important role in helping patients reduce anxiety during treatment. These findings indicate the importance of active family involvement in accompanying patients, both emotionally, informationally, and instrumentally. Therefore, educational programs involving families are highly recommended to improve the quality of care and support the psychological condition of cancer patients.